Work-Life Balance Strategies and their Influence on Employee Productivity - Pujowati, Endang Sri Eko; Aswan, Mukhamad Kholil (PT. Riset Press International, 2025)
The aim of this study is to explore the impact of work-life balance strategies on employee productivity and organizational well-being at Sekolah Luar Biasa Erha Pabelan. As work environments become increasingly flexible with the rise of remote and hybrid work models, it is essential to understand how these strategies influence both individual and organizational outcomes. This research adopts a qualitative approach, utilizing semi-structured interviews and focus group discussions with the principal, teachers and educational staff at Sekolah Luar Biasa Erha Pabelan. The data collected were analyzed through thematic analysis, identifying key themes related to flexible working arrangements, managerial support, wellness programs, and barriers to effective implementation. The findings reveal that flexible working hours and remote work options significantly enhance employee productivity and satisfaction, while supportive workplace culture and wellness programs further contribute to well-being and organizational engagement. However, challenges such as limited awareness of policies, resistance from middle management, and resource constraints hinder the full potential of these initiatives. The study concludes that organizations must proactively address these barriers and continuously adapt their strategies to foster a sustainable work-life balance. Future research should investigate the effectiveness of personalized work-life balance solutions, the role of technology in managing boundaries, and cross-cultural differences in the implementation of these strategies.